Bridging Communication Gaps: Enhancing Student-Teacher Interaction for Academic Success - Zobia Shakoor; Dr. Aabida Lateef; Dr. Sakhy Mehmood (Indus Journal of Social Sciences, 2025)
Effective communication is a fundamental determinant of academic success, serving as the cornerstone of the teaching-learning process, which is inherently interactive and dependent on the exchange of content and information. Communication gaps between teachers, students, and peers can significantly disrupt this process, impeding comprehension, engagement, and overall learning outcomes. Inadequate communication between teachers and students often correlates with diminished academic performance, underscoring the necessity of identifying and addressing the factors contributing to these gaps. The primary objective of this study was to investigate and analyze the underlying causes of communication gaps concerning students’ academic performance and to propose strategies for minimizing these barriers. A convenience sampling method was employed to select participating schools, while a simple random sampling technique was utilized to draw a sample of 160 students. Data were collected using a self-structured questionnaire based on a five-point Likert scale, designed to assess various dimensions of communication effectiveness. Descriptive statistical analysis was applied to interpret the collected data. The findings revealed that communication gaps exert a significant negative impact on students’ academic performance. Key contributing factors identified include lack of instructional clarity, teacher behavior issues, strained student-teacher relationships, psychological barriers, and emotional obstacles. Based on these findings, the study recommends targeted interventions to address these communication challenges. Implementing these strategies could enhance the quality of teacher-student interactions, thereby fostering a more conducive learning environment and promoting improved academic outcomes.